Optimalisasi Penggunaan Gandasil D Untuk Meningkatkan Produktivitas Tanaman Kale (Barassica Ileracea Var. Acephala) Pada Sistem Hidroponik - Alpyanto Sali; Tarsislus Jefri Lumalan; Fonny Patisa; Dirga Pabate; Sepsriyanti Kannapadang; Yusuf La’lang Limbongan; Willy Yavet Tandirerung; Adewidar Marano Pata’dungan (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
A research project entitled Optimisation of Gandasil D Use to Increase Kale (Barassica Oleracea Var. Acephala) Productivity in Hydroponic Systems was conducted at the Pakkea Experimental Garden, Faculty of Agriculture, North Toraja Regency, from March to June 2025. This research project aims to determine the response of Ab mix nutrients and Gandasil D fertiliser in the DFT system to the growth and production of kale plants. The method used in this study was a randomised block design (RAK) with 6 levels of Gandasil D concentration. (KO = Control), (K1 = 0.5 grams/litre of water), (K2 = 1 gram/litre of water), (K3 = 1.5 grams/litre of water), (K4 = 2 grams/litre of water), (K5 = 2.5 grams/litre of water) with 3 replications and with AB MIX concentrations, 0 to 7 days after planting = 400 ppm, 8 to 14 days after planting = 600 ppm, 15 to 21 days after planting = 800 ppm, 22 to 28 days after planting = 1000 ppm, 29 to 35 days after planting = 1200 ppm, 36 days and onwards until harvest = 1500 ppm. The variables observed in this study were plant height, leaf length, leaf width, number of leaves, and plant stem diameter. The results showed that a concentration of Gandasil D 2.5 grams/litre of water gave the best results with an average plant height of 37.93 cm, 12.56 leaves, leaf length of 24.16 cm, leaf width of 14.31 cm, stem diameter of 11.69 mm, and harvest weight of 232.89/plant. The data were analysed using analysis of variance (ANOVA) and followed by a post hoc test at a significance level of 0.05. The analysis of the feasibility of farming showed an R/C ratio of 1.03, which means that kale cultivation using a hydroponic system and the aforementioned nutrient concentration is feasible and profitable.